2005
DOI: 10.3758/bf03193069
|View full text |Cite
|
Sign up to set email alerts
|

Response selection involves executive control: Evidence from the selective interference paradigm

Abstract: In the present study, we investigated whether response selection involves executive control, using the selective interference paradigm within Baddeley's (1986) working memory framework. The interference from response selection was estimated by comparing the patterns of dual-task interference of simple and choice RT tasks with those of a number of established working memory tasks. In Experiment 1, we compared impairment of forward and backward verbal serial recall from the RT tasks and articulatory suppression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 51 publications
7
83
0
2
Order By: Relevance
“…In this task, a random sequence of low and high tones is presented at a random rate, and the participants are required to respond quickly by a corresponding keypress to each tone. Szmalec, Vandierendonck, and Kemps (2005) report a series of experiments showing that this task creates a moderate executive load while the effects of this load are dissociated from the effects of operations known to affect the slave systems in the model of Baddeley and Hitch (1974). The usefulness of the task has meanwhile been confirmed in several studies with mental arithmetic (e.g., Deschuyteneer & Vandierendonck, 2005a, 2005bDeschuyteneer, Vandierendonck, & Muyllaert, in press;Imbo, Vandierendonck, & Vergauwe, in press).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this task, a random sequence of low and high tones is presented at a random rate, and the participants are required to respond quickly by a corresponding keypress to each tone. Szmalec, Vandierendonck, and Kemps (2005) report a series of experiments showing that this task creates a moderate executive load while the effects of this load are dissociated from the effects of operations known to affect the slave systems in the model of Baddeley and Hitch (1974). The usefulness of the task has meanwhile been confirmed in several studies with mental arithmetic (e.g., Deschuyteneer & Vandierendonck, 2005a, 2005bDeschuyteneer, Vandierendonck, & Muyllaert, in press;Imbo, Vandierendonck, & Vergauwe, in press).…”
Section: Methodsmentioning
confidence: 96%
“…The duration of each tone was 200 ms. In a series of experiments, Szmalec et al (2005) have shown that this task taxes executive functioning, while the load on the subordinate workingmemory systems is negligible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tones were presented continuously during the complex arithmetic task. Szmalec, Vandierendonck, and Kemps (2005) have shown that this task interferes with the central executive, while the load on the slave systems is negligible. The CRT task was also performed alone (i.e., without the concurrent solving of arithmetic problems) for 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…In the latter condition, working memory was loaded by means of a Choice Reaction Time task (CRT task), where participants have to decide whether randomly presented tones are high or low. This task has been shown to interfere with executive functions of working memory, but not to tax slave systems of working memory (i.e., the phonological loop and the visuo-spatial sketch pad; Szmalec, Vandierendonck, & Kemps, 2005;Vandierendonck, De Vooght, & Van der Goten, 1998a, 1998bsee Schunn, Lovett, & Reder, 2001, for an analogous task). In particular, the CRT task affects the executive functions "input monitoring" (as the sequence of tones is unpredictable) and "decision making" (as participants have to decide whether the tone is high or low).…”
Section: Overview Of the Present Studymentioning
confidence: 99%